Apportionment of geochemistry, texture's properties, and risk assessment of some elements in surface sediments from Bardawil Lagoon, Egypt. Issue 3 (2nd April 2016) - Khalil, Mona Kh.; Draz, Suzanne E. O.; El Zokm, Gehan M.; El-Said, Ghada F.
ABSTRACT: Granulometric and geochemical analyses of surface sediment samples collected from twelve sites along Bardawil Lagoon [water content (A%; 15.88–71.38%), total organic carbon (TOC%; 0.12–6.76%), total carbonate (TCO3 %; 10.00–67.34%), total phosphorus (TP; 54.00–482.58 μg/g), sodium (Na; 2.65–8.99 mg/g), potassium (K; 0.63–2.54 mg/g), calcium (Ca; 23.33–201.20 mg/g), magnesium (Mg; 7.04–57.02 mg/g), fluoride (F; 1.00–680.47 μg/g), boron (B; 5.67–63.45 μg/g), Lithium (Li; 0.00–355.62 μg/g), Cobalt (Co; 0.00–15.48 μg/g), and bismuth (Bi; 2.12–15.09 μg/g)] were evaluated. The average results of the elements of geochemical parameters in the sediments gave a descending order of Ca > Mg > Na > K > F > Li > B > Bi > Co. The sediment pollution status was assigned by computing the enrichment factor with two methods concerning the usage of the crust's elements levels and a normalized element (Mg) and median of background values. The latter method reflected that the lagoon is still an uncontaminated region. The human health risk description was performed in the sediments using the exposure assessment of ingestion [(ExpIng ), dermal contact (ExpDerm ) and ingestion while swimming (ExpSwim )], hazard quotient (HQ), and hazard index (HI) for child and adult. The calculated Exp, HQ, and HI values reflected that the lagoon did not pose any risk to the populations.